An Evidence-Based Multidisciplinary Approach to the Management of Hepatocellular Carcinoma (HCC): The Alberta HCC Algorithm - Kelly W Burak; Norman M Kneteman (Canadian Journal of Gastroenterology)
Hepatocellular carcinoma (HCC) is one of only a few malignancies with an increasing incidence in North America. Because the vast majority of HCCs occur in the setting of a cirrhotic liver, management of this malignancy is best performed in a multidisciplinary group that recognizes the importance of liver function, as well as patient and tumour characteristics. The Barcelona Clinic Liver Cancer (BCLC) staging system is preferred for HCC because it incorporates the tumour characteristics (ie, tumour-node-metastasis stage), the patient’s performance status and liver function according to the Child-Turcotte-Pugh classification, and then links the BCLC stage to recommended therapeutic interventions. However, the BCLC algorithm does not recognize the potential role of radiofrequency ablation for very early stage HCC, the expanding role of liver transplantation in the management of HCC, the role of transarterial chemoembolization in single large tumours, the potential role of transarterial radioembolization with 90Yttrium and the limited evidence for using sorafenib in Child-Turcotte-Pugh class B cirrhotic patients. The current review article presents an evidence-based approach to the multidisciplinary management of HCC along with a new algorithm for the management of HCC that incorporates the BCLC staging system and the authors’ local selection criteria for resection, ablative techniques, liver transplantation, transarterial chemoembolization, transarterial radioembolization and sorafenib in Alberta.